2010
DOI: 10.1017/s0305000910000206
|View full text |Cite
|
Sign up to set email alerts
|

Cascading activation across levels of representation in children's lexical processing

Abstract: Recent work in adult psycholinguistics has demonstrated that activation of semantic representations begins long before phonological processing is complete. This incremental propagation of information across multiple levels of analysis is a hallmark of adult language processing but how does this ability develop? In two experiments, we elicit measures of incremental activation of semantic representations during word recognition in children. Fiveyear-olds were instructed to select a target (logs) while their eye-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 37 publications
8
57
2
Order By: Relevance
“…In contrast to previous research [11], our data do not support the notion that semantic information is activated in phonological cohort competitors either in clean or in noise. This is surprising given that even five-year olds have been shown to exhibited gaze behavior reflecting transient semantic competition in phonological cohort competitors in the clear [19]. We are confident to rule out that the lack of an effect is connected to statistical power as the present material set contained more items than most of the previous, comparable studies.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In contrast to previous research [11], our data do not support the notion that semantic information is activated in phonological cohort competitors either in clean or in noise. This is surprising given that even five-year olds have been shown to exhibited gaze behavior reflecting transient semantic competition in phonological cohort competitors in the clear [19]. We are confident to rule out that the lack of an effect is connected to statistical power as the present material set contained more items than most of the previous, comparable studies.…”
Section: Discussioncontrasting
confidence: 54%
“…We are confident to rule out that the lack of an effect is connected to statistical power as the present material set contained more items than most of the previous, comparable studies. A striking difference between the present and previous studies is that we chose an experimental design where the semantic competitor was presented along with three unrelated distractors as compared to being presented with either a depiction of the spoken target or a picture of the phonological competitor [11,19]. In the latter case, semantic activation in the phonological competitors could benefit from the visual input such that seeing a swan and a shield or seeing a sword and a shield in the same display prior to the critical spoken target ("swan") could provide a head start for activation to spread to semantic levels of representations.…”
Section: Discussionmentioning
confidence: 96%
“…To summarize these four visual world paradigm studies: all show that participants with low levels of language (adolescents with LI in [50,59]; older children with LI, with or without autism in [63]; typically developing 5-year-old children in [54]) show competition effects, consistent with the general core properties of lexical access and spoken word recognition outlined earlier. In all four studies, however, competition effects lurked for longer in individuals with lower levels of language skill.…”
Section: Lexical Processing In Language Impairmentsupporting
confidence: 58%
“…Although not yet tested in children with LI, Huang & Snedeker [54] present data from typically developing 5-yearold children that also point to competition effects lasting longer when language skills are relatively weak. Using the visual world paradigm, adults and children viewed scenes containing a target picture (e.g.…”
Section: Lexical Processing In Language Impairmentmentioning
confidence: 84%
“…Recent research has shown that typically developing children may have difficulties deactivating semantic competitors due to poor (not yet adult-like) inhibitory processing skills (Huang & Snedeker, 2011) or in the case of SLI an inefficient suppression mechanism (Andreu, Sanz-Torent, & Guardia-Olmos, 2012;Seiger-Gardner & Schwartz, 2008). Moreover, inhibitory mechanisms are developmentally constrained that is, as children get older they become better at inhibiting inappropriate lexical items from reaching sufficient activation to evoke selection and later retrieval (Hanauer & Brooks, 2005).…”
Section: Discussionmentioning
confidence: 99%